Cultivating empathy : inspiring health professionals to communicate more effectively - Stephany, Kathleen (Bentham Science Publishers Ltd., 2014)
Cultivating Empathy is perfect for any student or practicing health care professional who has felt that there was an absence of rapport when interacting with clients or patients and their families. Readers will gain awareness about human and emotional aspects of patient care, which will hopefully make a positive contribution to their professional practice.